2009
DOI: 10.1016/j.otohns.2009.06.078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microporous Polysaccharide Hemospheres (MPH) on Bleeding after Endoscopic Sinus Surgery

Abstract: The use of MPH after ESS results in significantly less bleeding in the early postoperative period with no increase in pain, obstruction, or nasal discharge. Patients treated with MPH follow a normal postoperative recovery otherwise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 16 publications
1
67
1
Order By: Relevance
“…This solution is used as a cell culture scaffold in basic research on regenerative medicine, and no reports to date have identified serious adverse effects in cultured cells or laboratory animals such as toxicity or carcinogenicity. 6,7) Unlike hemostatic agents such as oxidized cellulose or starch-based absorbent topical preparations that stem blood flow by the formation of clots, 8,9) the hemostatic action of TDM-621 is realized by modification of physical properties upon a change in pH to seal off the bleeding point in the same manner as an approved collagen-based absorbent topical hemostatic agent and physiological tissue adhesive (fibrin glue).…”
Section: Discussionmentioning
confidence: 99%
“…This solution is used as a cell culture scaffold in basic research on regenerative medicine, and no reports to date have identified serious adverse effects in cultured cells or laboratory animals such as toxicity or carcinogenicity. 6,7) Unlike hemostatic agents such as oxidized cellulose or starch-based absorbent topical preparations that stem blood flow by the formation of clots, 8,9) the hemostatic action of TDM-621 is realized by modification of physical properties upon a change in pH to seal off the bleeding point in the same manner as an approved collagen-based absorbent topical hemostatic agent and physiological tissue adhesive (fibrin glue).…”
Section: Discussionmentioning
confidence: 99%
“…[1268][1269][1270][1271] Three RCTs comparing packing to no-packing reported no evidence of significant postoperative bleeding requiring intervention in their unpacked arms. [1268][1269][1270] This is further supported by a large retrospective series by Orlandi and Lanza 1271 of 165 patients undergoing ESS. This study observed that only 11.2% of patients required packing at the end of their sinus procedure, with no reports of significant postoperative bleeding in those left unpacked.…”
Section: Xd5 Surgical Principles/techniques: Use Of Packingmentioning
confidence: 99%
“…Sinus surgery itself is not characteristically associated with significant amounts of pain, although patients do frequently report discomfort from nasal packing and its removal. Level 1 evidence suggests that packing with absorbable dressings such as Nasopore R , 1285 HemoStase R , 1270 Sepragel R , 1291 and Floseal R 1274 are not associated with any increased pain, compared to unpacked cavities. In fact, in the studies that evaluated Sepragel R and Floseal R , patients reported less subjective discomfort on the treated side.…”
Section: Xd5 Surgical Principles/techniques: Use Of Packingmentioning
confidence: 99%
“…There was a significant statistical difference between APH and the other subgroups as to bleeding time (p<0.001). MPH technology provides fast and effective hemostasis in endoscopic nasal sinus surgeries, [9] dermatologic surgeries, [11] and laparoscopic surgeries [12] with no serious sideeffects or postoperative complications. With the increase of minimally-invasive surgical procedures with risks of bleeding, the importance of topical hemostats has also increased.…”
Section: Discussionmentioning
confidence: 99%
“…It is hydrolyzed by histamine and degraded to amylase and glucoamylase and then completely resorbed. Clinically, MPHs have produced very successful results in endoscopic nasal sinus surgery, [9] dermatologic surgery, [10,11] and laparoscopic surgery, causing no serious complications intra-and postoperatively. [12] Formerly, the hemostatic agent APH has not been used against bleeding of tissue defect in patients under anticoagulant therapy.…”
Section: Introductionmentioning
confidence: 99%